An Efficient Reverse Converter for The New High Dynamic Range 5-Moduli Set - Xiaolan Lv; Ming Xiao (Institute of Advanced Engineering and Science, 2013)
In this paper, an efficient residue to binary converter design for the new high dynamic range moduli set 2n-1,2n+1,22n,22n+1,22n-1-1 is presented. The reverse conversion in the four-moduli set 22n, 22n+1, 2n+1, 2n-1 has been proposed in literature. Hence, the converters are based on the new moduli set 22n-1-1, (2n-1)(2n+1)(22n+1)22n and propose its residue to binary converter using New Chinese Remainder Theorem 2 ( New CRT 2). The new moduli set is proposed with a dynamic range 8n-1 bits and has the same features of the popular one. When compared to the common five moduli reverse converters, this enhanced moduli set has more dynamic range, and it useful for high performance computing. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3499